Defining dominion the discourses of magic and witchcraft in early modern France and Germany - Scholz Williams, Gerhild 1942- (Univ. of Michigan Press, 1995)
How did magic influence people's lives and thought in early modern Europe? How did woman come to be associated with magic and witchcraft and how did this affect her place in society? In this intriguing volume, Gerhild Scholz Williams explores the role of magic in France and Germany in the fifteenth and sixteenth centuries. She guides the reader through a variety of texts - many of them popular and influential in their day - and tells the story of how women were thrust into the center of a destructive discussion lasting several hundred years. This comprehensive study looks at magic as an intellectual and cultural language; as an attempt to explain the world, and as a means to control women whose propensity for satanic dalliance threatened not just their own souls but the health of the larger society. It will interest a wide variety of scholars and students of early modern culture, French and German literature, and gender and feminist studies.
Keywords: Geschichte 1400-1600; Hekserij; Magie; Geschichte; Magic -- France -- History; Magic -- Germany -- History; Witchcraft -- France -- History; Witchcraft -- Germany -- History; Hexerei; Deutschland; Frankreich